Engineering the morphology of hydrogen-bonded comb-shaped supramolecular polymers: from solution self-assembly to confined assembly. Issue 24 (4th June 2020) - Chen, Senbin; Geng, Zhen; Zheng, Xihuang; Xu, Jiangping; Binder, Wolfgang H.; Zhu, Jintao
Abstract : A library of nanostructures and multi-stage morphology transformation are realized by introducing a 3D confined assembly to hydrogen-bonded comb-shaped supramolecular polymer architectures. Abstract : Integrating three-dimensional (3D) confined assembly into hydrogen-bonded (H-bonded) supramolecular polymer architectures is a promising strategy, which can lead to unique nanostructures and expand the scope of applications for such an important library of polymers. Herein, comb-shaped hydrophobic supramolecular polymer architectures are constructed through H-bonding interactions, subsequently challenging their formation and multi-stage transition of water-dispersible nanostructures under 3D confinement. The cooperative yet compact polymeric phase segregation of the H-bonded comb-shaped supramolecular polymers via the confined assembly leads to the formation of spherical particles. The stepwise morphology transition ( e.g., from spheres with cylindrical internal structures to core–shell structures with a tunable shell thickness and a nanostructured core diameter, and finally to solid spheres) is realized by tuning the building block ratios and solvent evaporation temperature. Benefitting from the weak and dynamic nature of H-bonds, one building block is selectively removed while the other is maintained, affording specific nanostructures, including hollow spheres and particularly unprecedented random coil morphologies without resorting to invasive chemical degradation and cleavage. We believe that such approach provides a new opportunity toward compact supramolecular polymer assemblies with remarkable internal structures for potential applications in drug encapsulation, delivery and catalyst support.